Formant modification to improve intelligibility of dysarthric speech. (1st January 2011) - Nirupa, M.; Prema, P.; Vidhya, S.; Lazar Mathew, T.
Dysarthria is a motor speech disorder, characterised by poor articulation, resulting in speech which is slurred, slow and difficult to understand. The aim of this study is to understand the effects which formant frequencies have on the intelligibility of speech and to enhance the vowel region of the dysarthric speech, based on the modification of formants through linear predictive coding (LPC) analysis. The formants of the dysarthric speech are modified such that they closely match the normal target formants, without much variation in the pitch. The method adopted for formant modification retains the characteristics and naturalness of the speaker.